2020
DOI: 10.15294/dp.v15i1.23779
|View full text |Cite
|
Sign up to set email alerts
|

Digital Literacy in Formal Online Education: A Short Review

Abstract: This study aims to explain the current findings of digital literacy in formal online education. The methods of research is a type of library description  obtained from relevant scientific articles obtained from internet search media library engines: proquest, researchgate, google scholar and other search engines with keyword search "digital literacy" to find the publication of related scientific papers / relevant to the topic. Then the 41 articles found (listed in the references) are studied and then explained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0
23

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(63 citation statements)
references
References 15 publications
2
38
0
23
Order By: Relevance
“…The aforementioned study by Tejedor et al (2020) found the need to improve digital skills, especially communication, teaching, and methodology. The rationale behind this is that digital literacy can affect the output of learning outcomes on students' academic achievement (Yustika and Iswati, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The aforementioned study by Tejedor et al (2020) found the need to improve digital skills, especially communication, teaching, and methodology. The rationale behind this is that digital literacy can affect the output of learning outcomes on students' academic achievement (Yustika and Iswati, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, our students will have tremendous difficulty dealing with texts of various genres in multimedia packaging. Students who are only used to reading as "a way of re-encoding orthographic symbols silently or aloud" will be "overwhelmed" in dealing with complex texts presented by the PISA test (Yustika & Iswati, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…included in the concept of digital literacy extensively and its relationship to online learning academic performance. Beyond the primary purpose of bringing entertainment to the public from these social media platforms, active social media can influence learning in new ways that were never thought of before [8].…”
Section: Discussionmentioning
confidence: 99%
“…E-learning refers to the use of information and communication technology to allow access to online learning / teaching resources [15]. Higher levels of digital literacy positively affect high learning outcomes on student academic performance [8]. Digital literacy is a means to shape students' abilities to think analytically, synthetically, critically, imaginatively and creatively.…”
Section: I G I T a L L I T E R A C Ymentioning
confidence: 99%